A study of quality of service in the universal DBA algorithm using a PIC-based EPON testbed - Radzi N.A.M.; Din N.M.; Al-Mansoori M.H.; Sadon S.K.; Majid M.S.A. (Kluwer Academic Publishers, 2023)
Ethernet Passive Optical Network (EPON) has emerged as a promising technology since it offers high bandwidth at a distance that can go up to 20 km. In the upstream EPON transmission, a dynamic bandwidth allocation (DBA) algorithm is needed to avoid collisions and to efficiently allocate the bandwidth. This paper proposes an algorithm called as a Universal DBA (UDBA) algorithm that can support the priority universally in the entire EPON system. A peripheral interface controller (PIC)-based EPON testbed is used to test the algorithm within the mulipoint control protocol environment. For the performance study, we have compared the results achieved using UDBA in terms of delay, throughput, and fairness with two other DBA algorithms. UDBA shows improvements in terms of expedited forwarding, assured forwarding and best effort delay as much as 43.9, 42.6, 20 % over User-oriented Hierarchical Bandwidth Scheduling with Single Cycle (UHSA-S) and 37.5, 20.2, 25.3 % over Modified Smallest Available Report First (MSARF), respectively. Throughput is improved as high as 17.9 % over UHSA-S and 12.8 % over MSARF. In addition, the fairness index of UDBA is higher up to 14 % as compared to UHSA-S and 2.7 % as compared to MSARF. © 2013 Springer Science+Business Media New York.